2001
DOI: 10.1176/appi.ajp.158.12.2056
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Women Who Stalk

Abstract: Female and male stalkers vary according to the motivation for their pursuit and their choice of victim. A female stalker typically seeks to attain a close intimacy with her victim, who usually is someone previously known and frequently is a person cast in the professional role of helper. While the contexts for stalking may differ by gender, the intrusiveness of the behaviors and potential for harm does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 23 publications
8
162
0
11
Order By: Relevance
“…The limited number of studies that addressed gender differences tend to report few differences with respect to the variables discussed in this study. For example, female stalkers are less likely to have a history of criminal offenses than male stalkers, but male and female stalkers are equally likely to have personality disorders (Purcell, Pathé, & Mullen, 2001). Further, the positive associations between stalking perpetration and borderline traits (Lewis et al, 2001), obsessive thoughts about the ex-partner (Davis et al, 2000), anxious attachment (Davis et al, 2000;Dye & Davis, 2003;Lewis et al, 2001), and being the recipient of the breakup (Dye & Davis, 2003) have been found to be similar for men and women.…”
Section: Risk Factors Of Upbmentioning
confidence: 97%
“…The limited number of studies that addressed gender differences tend to report few differences with respect to the variables discussed in this study. For example, female stalkers are less likely to have a history of criminal offenses than male stalkers, but male and female stalkers are equally likely to have personality disorders (Purcell, Pathé, & Mullen, 2001). Further, the positive associations between stalking perpetration and borderline traits (Lewis et al, 2001), obsessive thoughts about the ex-partner (Davis et al, 2000), anxious attachment (Davis et al, 2000;Dye & Davis, 2003;Lewis et al, 2001), and being the recipient of the breakup (Dye & Davis, 2003) have been found to be similar for men and women.…”
Section: Risk Factors Of Upbmentioning
confidence: 97%
“…[8][9][10][11][12] This is a constant in the scientific literature, even if stalking is not considered a gender-specific behavior. 1 The most common type of stalker is the ex-partner who refuses to accept that the relationship is at an end, 13 but the percentage of women harassers of their ex-partner seems to be markedly lower than that of their male counterparts. In a study based on the data of the "National Violence against Women Survey" of 1998, representing the adult US population, Slashinski et al 14 calculated that only 1.6% of males had suffered stalking by their female ex-partner.…”
Section: Female Stalking: An Overviewmentioning
confidence: 99%
“…1,19 In particular, in a study by Purcell et al, 1 that lasted 8 years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) and was conducted in a sample of 190 stalkers at a community forensic mental health clinic specializing in the assessment and treatment of stalkers and their victims, 21% of the stalkers were women.…”
Section: Female Stalking: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations